Learning Design of Islamic Religious Education for Elementary Schools: Integrative Review - Cerda Urika (Ruhama : Islamic Education Journal, 2022)
Learning design is the most important part of planning the goals to be achieved, while the condition of the learning design of Islamic religious education at the elementary school level in Bathin Solapan District has not been uniformed. In accordance with this problem, this study aims to analyze the learning design of Islamic religious education. The results of research conducted at the Bathin Solapan Subdistrict Elementary School showed that the design of the PAI teacher learning program was in accordance with the standards set, but in terms of formulating learning indicators and objectives, there were still weaknesses found, the difference between indicators and learning objectives, which should be between indicators and learning objectives must be the same in learning tools. However, it causes a problem for PAI teachers and PAI teachers always depend on the teacher's working group. So that PAI teachers in making learning tools need to be accompanied by the principal or even the supervisor to monitor directly.